Christological "Once for All" of the Revelation versus Marian Dogmas in Joseph Ratzinger’s Theology - Sławomir Zatwardnicki (Wrocławski Przegląd Teologiczny)
The purpose of this article is to show Marian dogmas in their relationship to Scripture as a testimony of revelation and to Tradition. In the first part, the author clarifies Ratzinger’s account of the relationship between the uniqueness of revelation in Christ and its continuity, as well as the links between Scripture preserving the “once for all” of revelation with Tradition, in which revelation is always present. The second part addresses the question of the Church’s memory, in which the Holy Spirit, guiding to all truth, also revealed the Marian aspect of revelation. Furthermore, the dynamic concept of Tradition demanded by the promulgation of the Marian dogmas of 1854 and 1950 is presented. In the last and most important part of the article, the author extracted from the work of the Bavarian theologian those contents of Mariology which, originating from the seeds of the inspired texts, shed light on the “once” of revelation and its testimony in Scripture. The example of Marian dogmas serves the purpose of outlining the creative though strained relationship between the two poles of revelation: uniqueness and continuity.